Karyotypic analysis on three edible Allium species from Bangladesh (Bangladesh Journal of Botany, 2022)
Three edible species of Allium, namely, A. sativum, A. cepa and A. tuberosum were cytogenetically investigated to highlight the chromosomal variations among them. These three species of Allium revealed two different numbers of chromosomes with divergent karyotype formula i.e. 2n = 16 = 12m + 4sm in A. sativum, 2n = 16 = 14m + 2sm in A. cepa and 2n = 32 = 28m + 2sm+ 2st in A. tuberosum. A pair of satellite chromosome was found only in A. tuberosum. According to Stebbins’s classification 1B (A. sativum) and 2A (A. cepa and A. tuberosum) type of chromosomal asymmetry were observed. The present cytogenetical analysis revealed that A. cepa was primitive in nature compared to other two species. A. sativum was found to be contemporary to A. cepa and A. tuberosum was more advanced type.Bangladesh J. Bot. 51(2): 353-358, 2022 (June)